2016
DOI: 10.1155/2016/4269431
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity and Fractal Properties of Climate Change during the Past 500 Years in Northwestern China

Abstract: By using detrended fluctuation analysis (DFA), the present paper analyzed the nonlinearity and fractal properties of tree-ring records from two types of trees in northwestern China, and then we disclosed climate change characteristics during the past 500 years in this area. The results indicate that climate change in northwestern China displayed a long-range correlation (LRC), which can exist over time span of 100 years or longer. This conclusion provides a theoretical basis for long-term climate predictions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In Bénin, at the synoptic scale, DFA2 is the best method in terms of spatial average. is result confirms those of [6,24]. ese authors have found the second-order DFA (DFA2) method as the best and the most commonly used order, respectively, for outgoing longwave and temperature records.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In Bénin, at the synoptic scale, DFA2 is the best method in terms of spatial average. is result confirms those of [6,24]. ese authors have found the second-order DFA (DFA2) method as the best and the most commonly used order, respectively, for outgoing longwave and temperature records.…”
Section: Discussionsupporting
confidence: 81%
“…e multifractal detrended fluctuation analysis (MFDFA) method is a generalization of the standard DFA method. It is generally preferred and widely used in the literature to detect the fractal scaling properties of the mth-order moments and long-term memory in nonstationary and nonlinear time series as, meteorological and climatological series [6,24,25]. e modified MFDFA procedure consists of a sequence of steps and detailed information about computation can be found in [26].…”
Section: Description Of the Mfdfa Methodmentioning
confidence: 99%
“…To investigate multifractal characteristics of non-stationary, non-linear, natural and complex meteorological phenomenon time series (Shen et al, 2015(Shen et al, , 2017Wan et al, 2016;, the MFDFA method was proposed If the time series follow the power law, then we can obtain the scaling function:…”
Section: Description Of Mfdfa Methodsmentioning
confidence: 99%
“…To investigate multifractal characteristics of non-stationary, nonlinear, natural, and complex meteorological phenomenon time series (Shen et al 2017;Wan et al 2016;Jiang et al 2017), the MFDFA method was proposed by Kantelhardt et al (2002). It can be briefly described as follows (Shen et al 2017):…”
Section: Multifractal Detrended Fluctuation Analysismentioning
confidence: 99%